IMPACT OF PHARMACIST INTERVENTION IN SCREENING AND EDUCATION ON BLOOD PRESSURE IN A RURAL AREA IN SOUTHERN INDIA - Kandasamy, Krishnaveni; Natarajan, Agilan; Sebastian, Joyal; Konakalla, Manikanta; Sam, Rohit; Rajagopal, Shanmuga Sundaram; Ramathan, Sambathkumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Hypertension (HTN) expends a consequential public health concern on cardiovascular health status and health-care systems in India. The effectuation of the pharmaceutical care program in the health care is an extremely important need to achieve the optimum therapeutic effect. The objective of the study was to assess the impact of pharmacist intervention on patient’s blood pressure (BP) level, quality of life (QOL), and knowledge, attitude, and practice (KAP) of hypertensive patients. Methods: A randomized controlled pilot study was carried out for 6 months. The hypertensive patients were randomized into control and intervention group based on age, and both the groups were interviewed using KAP and WHO QOL-BREF questionnaires, screened BP, respectively, at baseline and each follow-up after post counseling section to the intervention group. The effect of pharmacist intervention on QOL and KAP among control and intervention was statistically analyzed by paired t-test using SPSS version 16. Results: The total sample studied was 60, of which 20 (33.33%) were males and 40 (66.67%) were females. In our study, the QOL score for each domain of both intervention and control groups were almost poor (pËƒ0.05) at baseline and for the intervention group, a highly significant improvement (p<0.001) was observed for all domains in final follow-up. KAP score of intervention group also showed a significant improvement (p<0.001) from baseline to final follow-up. In this study, intervention group showed a significant mean reduction of systolic BP from baseline 150.13Â±25.670 to final follow-up 145.33Â±12.914. Conclusion: The results of the study showed a significant improvement in the patient’s KAP toward different aspects of HTN and QOL following pharmacist mediated counseling. Involvement of pharmacy practitioners in the management of HTN significantly improves QOL and KAPs. Keywords: Hypertension, Quality of life, Knowledge, Attitude and practice, Pharmacist intervention, Patient counseling.